Quantifying session ratings of perceived exertion for field-based speed training methods in team sport athletes - Lockie, R. G.; Murphy, A. J.; Scott, B. R.; Janse de Jonge, X. A. K. (The Journal of Strength and Conditioning Research, 2012)
Session ratings of perceived exertion (session RPE) are commonly used to assess global training intensity for team sports. However, there is little research quantifying the intensity of field-based training protocols for speed development. The study's aim was to determine the session RPE of popular training protocols (free sprint [FST], resisted sprint [RST], and plyometrics [PT]) designed to improve sprint acceleration over 10 m in team sport athletes. Twenty-seven men (age = 23.3 ± 4.7 years; mass = 84.5 ± 8.9 kg; height = 1.83 ± 0.07 m) were divided into 3 groups according to 10-m velocity. Training consisted of an incremental program featuring two 1-hour sessions per week for 6 weeks. Subjects recorded session RPE 30 minutes post training using the Borg category-ratio 10 scale. Repeated measures analysis of variance found significant (p < 0.05) changes in sprint velocity and session RPE over 6 weeks. All groups significantly increased 0- to 5-m velocity and 0- to 10-m velocity by 4-7%, with no differences between groups. There were no significant differences in session RPE between the groups, suggesting that protocols were matched for intensity. Session RPE significantly increased over the 6 weeks for all groups, ranging from 3.75 to 5.50. This equated to intensities of somewhat hard to hard. Post hoc testing revealed few significant weekly increases, suggesting that session RPE may not be sensitive to weekly load increases in sprint and plyometric training programs. Another explanation, however, could be that the weekly load increments used were not great enough to increase perceived exertion. Nonetheless, the progressive overload of each program was sufficient to improve 10-m sprint performance. The session RPE values from the present study could be used to assess workload for speed training periodization within a team sports conditioning program.